Obstacles experienced by school counselors in the implementation of guidance and counseling service programs - Khairunisa Khairunisa; Neviyarni Neviyarni; Riska Ahmad (Journal of Counseling, Education and Society, 2022)
This research was conducted on the coordinator of school counselors at state high schools and private high schools in Medan City. This study aims to determine the obstacles experienced by school counselors in the implementation of guidance and counseling service programs. This research is a descriptive research with a quantitative approach and survey methods. The collection technique used in this study was a questionnaire on the Guttman scale. The subjects in this study were 30 school counselor coordinators, including 15 school counselor coordinators at State High Schools and 15 school counselor coordinators at Private High Schools in Medan City. The results of this study showed that the obstacles experienced by school counselors in internal factors in the aspect of teacher competence showed higher results (50%) than aspects of personality and dedication (17%). Meanwhile, external factors in the aspect of facilities and infrastructure showed higher results (47%) than aspects of economic welfare (13%). The understanding and lack of professionalism of school counselors causes this to be one of the weaknesses of teachers in conducting counseling programs.